Crustal deformation from geodetic techniques: Earthquakes and plate movements in the South Iceland Seismic Zone - Decriem, Judicael (2011)
The South Iceland Seismic Zone (SISZ) is one of the most seismically active area in Iceland. The last two major events occured in the central and western parts of the SISZ in June 2000 and May 2008, respectively. In this thesis, I use geodetic methods to estimate the deformation due to earthquakes and plate spreading and derive models of the crustal processes. In the first paper we derive a uniform-slip and a variable-slip fault models for the two 29 May 2008 earthquakes based on GPS and InSAR observations.We account for the variation in the elastic parameters of the crust with depth. Our models indicate that the slip for the first event (Ingolfsfjall) was concentrated at 2-4 km depth, with a maximum of 1.9 m, whereas the slip on the second fault (Kross) was located deeper, at 3-6 km depth with up to 1.4 m of motion. Static Coulomb failure stress calculations indicate that the first event caused a stress increase in the area of the main asperity on the second fault. We estimated a composite moment that equals a Mw 6.1 for the doublet. We also find that the June 2000 - May 2008 sequence only released about half of the moment accumulated by plate motion since the previous earthquake sequence in the SISZ during 1896-1912. In the second paper we document the transient following the June 2000 earthquakes, extending a previous study with GPS data from 2004 to 2008. We explore whether viscoelastic models based on Maxwell and/or standard linear solid (SLS) rheologies can reproduce the surface velocities observed during 2000-2008 and calculate the corresponding stress changes. Our preferred model consists of a ~15 km thick elastic crust overlying a SLS upper mantle with a viscosity of 1-2*10E18 and relaxation strength between 0.1-0.25. The viscoelastic transient promotes failure in the area of the May 2008 earthquake. However, the Coulomb failure stress changes due to the viscoelastic relaxation are very small (0.05 MPa) compared to the static stress changes from the June 2000 main shocks. Viscoelastic loading may ...